Physiological, ultrastructural, biochemical, and molecular responses of glandless cotton to hexavalent chromium (Cr6+) exposure. (November 2020) - Samrana, Samrana; Ali, Abid; Muhammad, Uzair; Azizullah, Azizullah; Ali, Hamid; Khan, Mumtaz; Naz, Shama; Khan, Muhammad Daud; Zhu, Shuijin; Chen, Jinhong
Abstract: Glandless cotton can be grown to obtain cotton seeds free of toxic gossypol for use as both food and feed. However, they are not grown normally due to their lesser productivity and higher susceptibility to biotic stress. Great attention has been paid to biotic stresses rather than abiotic stresses on glandless cotton. Chromium (Cr) is a common pollutant of soil and considered a serious threat to plants due to its adverse effects on different functions. Although numerous studies are available on the toxicity of Cr 6+ in various plants. However, its adverse effects and mechanism of toxicity in glandless cotton can seldom be found in the literature. This study examined the Cr 6+ effect on glandless cotton in comparison to glanded cotton. Four pairs of glanded and glandless cotton near-isogenic lines (NILs) were exposed to different doses (0, 10, 50, and 100 μM/L) of Cr 6+ for seven days, and biochemical, physiological, molecular, and ultrastructure changes were observed, which were significantly affected by Cr 6+ at high concentrations in all NILs. The effect of Cr 6+ on ionic contents shows the same trend in glanded and glandless NILs except for manganese (Mn 2+ ) that show inhibition in glandless (ZMS-12w and Coker-312w) and enhance in the glanded NIL (ZMS-17). The gene expression of superoxide dismutase (SOD) and peroxidase (POD) revealed similar trends as enzyme activities in glandless NILs. The principal component analysis (PCA) and Agglomerative hierarchical clustering (AHC) results of all NILs from morpho-physiological traits, cluster ZMS-16, and ZMS-17 into Cr 6+ sensitive group. While the glandless NILs have the potential to cope with the Cr toxicity by increasing the antioxidant enzyme activity and their gene expression. This study also revealed that Cr 6+ tolerance in cotton is genotypic and has an independent mechanism in the root that not related to low gossypol. Graphical abstract: Image 1 Highlights: Chromium (Cr) adversely affects plant growth and root morphology. Cr impaired nutrients uptake and enhance H2 O2 that leads to ultrastructure damages. Cr-induced phytotoxicity varied among cotton near-isogenic lines (NILs). Glandless cotton shows more resistance to Cr stress as compared to glanded cotton.